Alleviation of Oxidative Stress and Suppression of Inflammatory Cytokines in STZ -induced Diabetes by Banana (Musa paradisiacal), Kiwi (Actinidiadeliciosa planch) and Olive (OleaeuropaeaL.), by-products, Extract: Comparative Study - Hanan F. Aly (Journal of Global Pharma Technology, 2019)
The effect of peels (kiwi, banana and leaves (olive and banana)acetone extract 80%on streptozotocin (STZ) induced diabetic rats was investigated. Oral administration of 500 mg crude extract /kg body weight for 30 days post induction of diabetes, showed remarkable improvement in all biomarkers under investigation compared to standard drug. Olive leaves showed the highest percentage of improvement in glutathione (GSH), nitric oxide, (NO), glutathione peroxidase (GPX) glutathione –S-transferase (GST) ,catalase, lipid peroxide (MDA) , urea  ,creatinine, tumor necrosis factor- α(TNF-α) interleukin 1β(IL1-β)  (41.74,138.68, 48.77, 26.15, 27.84, 73.54, 97.92, 81.37, 52.96 and 40.24% , respectively).While, banana leaves and kiwi peels extracts showed the highest percentage of improvement in antioxidant enzyme paraoxonase (PON1) and transforming growth factor β(TGF β)reached  16.90 and 41.81%, respectively. From a histopathological point of view, treatment of diabetic rats with different extracts revealed regeneration and amelioration effects of extracts on the pancreas and renal tissues in diabetic rats and apparently normal. It could be concluded that the anti-hyperglycemic properties of plant extracts may offer a potential therapeutic source for the treatment of diabetes. Further work on isolation and characterization of active constituents in these wastes is needed.Keywords: Diabetes, Inflammatory cytokines, Antioxidant, Oxidative stress.